STUDENTS’ INTERACTION IN MEMORIZING VOCABULARY THROUGH TOTAL PHYSICAL RESPONSE METHOD - Rita Harisma; Chaimah Rosalia Simanjuntak (Universitas Muria Kudus, 2021)
This study was to analysed the students’ interactions in memorizing vocabulary through Total Physical Response (TPR) Method. The researcher used qualitative descriptive research as the method of this study. The research data were collected by using the interview, questionnaires, and document. This research had been done to the first grade students of SMP Negeri 18 Medan, consisting of 33 students that were taken from one class. All the population were taken as the sample of the research. The instrument of the research was questionnaires sheet to analyzing students’ interaction in vocabulary through Total Physical Response (TPR) Method. It was to found the students’ interactions in memorizing vocabulary and most dominant of command and prohibition. Based on questionnaires that, the data got some benefits to TPR method that is to having fun of learning process and increasing the ability of students’ interactions to learning vocabulary with command and prohibition sentence. The results of this study indicate that learning is more active for students in learning and is able to increase interaction between students in solving problems in learning through discussion and the use of vocabulary and the use of command sentences.